Challenges in the Implementation of Radicalism Prevention Policy in Elementary Education Schools in Garut Regency - Muhammad Rizki Joyonegoro; Ida Widianingsih; R. Widya Setiabudi Sumadinata (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
This study is the result of research on the implementation of radicalism prevention policies through the independent curriculum P5 project in elementary level education schools in Garut Regency. This research is also motivated by the author's interest in radicalism prevention policies, especially among young people. The Garut Regency Government has issued Garut Regent Regulation Number 143 of 2023 concerning the Regional Action Plan for Preventing and Combating Violent Extremism that Leads to Terrorism, one of which aims to prevent radicalism in the school environment due to concerns about the spread of radicalism among young people. This research uses a qualitative research method with a descriptive approach. Data were obtained through literature study and field study (observation and interview). The data validity technique used was the triangulation of sources and methods. The results of this study indicate that there are several challenges faced by policy actors in policy implementation such as limited human resources, the influence of the environment and local culture, the wide area of distribution of primary level education schools and low parental participation.